Factors Mediating HIV Risk among Female Sex Workers in Europe : A Systematic Review and Ecological Analysis - Platt, Lucy; Jolley, Emma; Rhodes, Tim; Hope, Vivian; Latypov, Alisher; Reynolds, Lucy; Wilson, David (BMJ Publishing Group, 2015)
We reviewed the epidemiology of HIV and selected sexually transmitted infections (STIs) among female sex workers (FSWs) in WHO-defined Europe. There were three objectives: (1) to assess the prevalence of HIV and STIs (chlamydia, syphilis and gonorrhoea); (2) to describe structural and individual-level risk factors associated with prevalence and (3) to examine the relationship between structural-level factors and national estimates of HIV prevalence among FSWs.